Radar foundations for imaging and advanced concepts - Sullivan, Roger J., 1941- (SciTech radar and defense series., 2004)
The book reviews developments in the following fields: radar fundamentals; radar imaging; synthetic aperture radar; SAR; STAP; air-to-air radar; bistatic radar; low-probability of intercept radar; LPI radar; weather radar; ground-penetrating radar; GPR; pulse-Doppler radar; and MTI radar.